Fabrication Methods of Porous Carbon Materials and Separator Membranes for Lithium–Sulfur Batteries: Development and Future Perspectives. Issue 8 (17th July 2017) - Wang, Tianyi; Kretschmer, Katja; Choi, Sinho; Pang, Huan; Xue, Huaiguo; Wang, Guoxiu
Abstract : Lithium–sulfur batteries (Li–S batteries) have a five times higher energy density than state‐of‐the‐art lithium‐ion batteries and have attracted world‐wide attention. However, many inherent problems limit the practical application of Li–S batteries. Among them, the dissolution of polysulfides, which is called the "shuttle effect", is rather severe and usually causes irreversible capacity decay. Many methods have been developed to overcome this problem, including the rational design of porous cathode hosts, modification of separators to prevent the migration of polysulfides, and the addition of transition‐metal oxides for polysulfide adsorption. Here, the various preparation methods for the development of high performance Li–S batteries are reviewed. The advantages and disadvantages of each method are discussed in detail, shedding light on directions for further research and development in the future. Abstract : Li–S batteries represent a new generation of rechargeable lithium batteries for many applications, such as portable electronics, electric vehicles, and large‐scale energy storage and conversion. A comprehensive review on the various fabrication methods of preparing porous cathode materials and modifying separator membranes for high‐performance Li–S batteries is presented.